Evaluation of Paid Parking Performance at Station Bojonggede - Syaiful, Syaiful; Anggi, Muhamad (ASTONJADRO, 2024)
The Bojonggede station parking lot is currently less efficient because it does not have enough land for parking needs. So this research aims to determine the capacity of parking space requirements at Bojonggede station. In this research, the characteristic SRP method is used (Volume, Accumulation, Duration, Turnover, Index). In this research, it is the performance management of paid parking. Data collection was carried out using a survey method over 12 hours and running for fifteen days, with the data taken being data on vehicle entry and exit times to determine the characteristics of the parking lot. The results of this research are that the existing capacity of motorbike parking spaces at Bojonggede station is 300 SRP with an area of 715m² which cannot accommodate parked motorbikes, with the research results getting an index figure of more than 100%, namely parking turnover of 217% at peak hours. . The result of the SRP requirement that must be provided by the management is 448 slots to accommodate motorbikes. There are additional official signs from PT. KAI, for example with no parking signs in the parking circulation area, has added parking officers to arrange and position motorbikes, so that parking circulation can be facilitated.